"Alle Apparate abschalten." Conceiving Love and Technology with Heidegger And Kittler - Winkler, Robert A.; Justus Liebig University Giessen (My University, 2020)
This article explores Friedrich Kittler´s conception of the intersection of love with modern technology and illustrates the theoretical insights gained by considering Spike Jonze´s film Her (2013). The German media theorist Friedrich Kittler (1943 2011) was among the first to study the discursive and material implications of modern technologies. Recent scholarship has stressed Kittler s indebtedness to Martin Heidegger´s philosophy of technology. Accordingly, Kittler thinks through the latter´s contention that it is in and through modern technology that human beings are possibly confronted with truth events, in which the particular time-specific self-unconcealment of being takes place and this unconcealment would not least materialize in the realm of love (Gumbrecht 2013; Kittler 2014; Weber 2018).In this article, I focus on the theoretical examination of Heidegger´s philosophy of technology in general and the concomitant notion of enframing in particular to shed further light on Kittler´s reflection on love that pervades the latter´s entire oeuvre. The article then interrogates whether, and under what circumstances, modern technology might foster said truth events by focusing on: first, love among human beings, second, love among technological beings, and, third, love between human beings and technological beings. Thereby, Spike Jonze´s critically acclaimed science-fiction drama Her, depicting a romantic relationship between a human being and a computer operating system, serves as a reference point in illustrating Kittler´s multifaceted conception of the nexus of love and modern technology.
Keywords: Friedrich A. Kittler; love; technology; Martin Heidegger; popular culture studies; ddc:300